Įkaitas LDK teisėje iki Pirmojo Lietuvos Statuto (1529 m.) - Steponavičienė, Lirija (Lietuvos istorijos studijos, 2024)
The hostage institution in the Law of the Grand Duchy of Lithuania has got an exhaustive historiography, that's why the manifestation of this institution in the earliest written source of GDL and the regulation of its standards up to the First Lithuanian Statute is discussed in this article.The information about the hostage up to the middle of the 15th century is fragmentary (the exception is the privilege of Duke Vytautas to the Brasta Jewish community in 1388). However, in the 2nd half of the 15th century - the beginning of the 16th century, the acts of the Lithuanian Metrica and other acts allow us to disclose the essence of the hostage, the object and the subject of the hostage law, the continuation, the procedure of return of the hostage, and so on.The First Lithuanian Statute legalized the main standards of the hostage law, though they were reflected in a many-sided way in court practice.